Li17Sb13S28: A New Lithium Ion Conductor and addition to the Phase Diagram Li2S–Sb2S3. Issue 39 (11th August 2015) - Huber, Sebastian; Pfitzner, Arno
Abstract Li17Sb13S28 was synthesized by solid‐state reaction of stoichiometric amounts of anhydrous Li2S and Sb2S3. The crystal structure of Li17Sb13S28 was determined from dark‐red single crystals at room temperature. The title compound crystallizes in the monoclinic space group C2/m (no. 12) with a=12.765(2) Å, b=11.6195(8) Å, c=9.2564(9) Å, β=119.665(6)°, V=1193.0(2) Å3, and Z=4 (data at 20 °C, lattice constants from powder diffraction). The crystal structure contains one cation site with a mixed occupation by Li and Sb, and one with an antimony split position. Antimony and sulfur form slightly distorted tetragonal bipyramidal [SbS5E] units (E=free electron pair). Six of these units are arranged around a vacancy in the anion substructure. The lone electron pairs E of the antimony(III) cations are arranged around these vacancies. Thus, a variant of the rock salt structure type with ordered vacancies in the anionic substructure results. Impedance spectroscopic measurements of Li17Sb13S28 show a specific conductivity of 2.9×10−9 Ω−1 cm−1 at 323 K and of 7.9×10−6 Ω−1 cm−1 at 563 K, the corresponding activation energy is EA=0.4 eV below 403 K and EA=0.6 eV above. Raman spectra are dominated by the SbS stretching modes of the [SbS5] units at 315 and 341 cm−1 at room temperature. Differential thermal analysis (DTA) measurements of Li17Sb13S28 indicate peritectic melting at 854 K.